Oral-motor therapy - Maria Elena Widman Valencia; Damaris Estrella Castillo; Lizzette Gómez De Regil (Colegio Colombiano de Terapia Ocupacional, 2024)
Eating and swallowing disorders are prevalent among children with neuromotor disabilities, significantly impacting their overall quality of life. The COVID-19 pandemic exacerbated the challenges by restricting access to health care, underscoring the necessity for innovative solutions with caregiver involvement. This study investigated the effectiveness of a distance learning educational model in oral-motor therapy for primary caregivers of children with neuromotor impairments in Mérida, Mexico. The quasi-experimental pretest-posttest design included thirty primary caregivers of children aged 2 to 12 with feeding and swallowing disorders from seven institutions. Twenty-three participants completed the program. The program encompassed theoretical sessions on various aspects of oral motor therapy and practical sessions focusing on hands-on training. Results revealed substantial enhancements in theoretical knowledge and practical competencies among caregivers, with competence levels exceeding 80% in all evaluated activities. Despite these positive outcomes, the study acknowledges limitations such as a small sample size and the absence of a control group. Addressing these constraints through future research endeavors will bolster the evidence supporting the effectiveness of this innovative caregiver-centric approach. Ultimately, integrating caregivers into the care team is imperative for improving the quality of life for children with neuromotor disabilities and effectively managing eating and swallowing disorders.